PENGARUH KARAKTERISTIK SASARAN PENGANGGARAN TERHADAP KINERJA MANAJERIAL (Studi Empiris Bank-Bank Di Daerah Istimewa Yogyakarta) - Putri, Caesar Marga (Jurnal Manajemen Magister Darmajaya, 2017)
Budget is a planning and control tool. As a control tool, budget measure magerial performance by comparing the actual performance and the budget so efficiency and effectivity can be identified. In budgeting, involvement of human behavior aspect of individuals that taking part in budgeting must be focused. Behavioral aspect that involved in budgeting refer to budgeting goal characteristic: budgetary participation, budget goal difficulty, budgetary evaluation (supportive and punitive), budgetary feedback andbudget goal clarity. The five aspects of budgeting goal characteristicare espected having an effect on managerial performance. This study focused on the managerial performance on bank sector in Yogyakarta region. The result shows that five characteristics of budgeting goal characteristic have a positive effect on managerial performance.Â Keywords: budgetary participation, budget goal difficulty, budgetary evaluation (supportive and punitive), budgetary feedback and budget goal clarity, managerial performance.